2020
DOI: 10.18805/ijare.a-576
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wheat to Foliar and Soil P Fertilization on Grain Yield and Phosphorus use Efficiency in Southeastern Algeria

Abstract: Background: P deficiency is very common in alkaline - calcareous soil. Therefore, application of foliar-absorbed fertilizers may be an effective strategy to overcome the low bioavailability of phosphorus in soil, by improving phosphorus use efficiency and reduced nutrients loses.Methods: A field experiment was carried out in 2006-07 growing season at El-Menia (southeastern Algeria) to evaluated the effect of two foliar P (agriphos and leader-start) and three soil P (TSP P 46, Fosfactyl NP 3:22 and NPKs 8:36:13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…This is supported by Lalani (2000) who reported that an increase in the latex yield due to fertiliser application can have a direct effect on girth size, growth of bark, bark renewal and canopy maintenance. Phosphorus is one of the most common nutrients for growth and development Boukhalfa-Deraoui (2021). This is similar to the result of a study conducted by Tiva et al (2016) which pointed out that improved latex yield and plant physiological condition change due to fertilisation.…”
Section: Resultssupporting
confidence: 87%
“…This is supported by Lalani (2000) who reported that an increase in the latex yield due to fertiliser application can have a direct effect on girth size, growth of bark, bark renewal and canopy maintenance. Phosphorus is one of the most common nutrients for growth and development Boukhalfa-Deraoui (2021). This is similar to the result of a study conducted by Tiva et al (2016) which pointed out that improved latex yield and plant physiological condition change due to fertilisation.…”
Section: Resultssupporting
confidence: 87%
“…When Phosphorous fertilizer is added to calcareous soils, a series of fixation reactions occur and gradually decrease its solubility and eventually its availability to plants [24]. Limestone affects the pH of the soil which in turn influences phosphorus assimilation [25] by forming insoluble Ca-P which is considered the main factor of phosphorus unavailability [26]. A good technical itinerary of fertilization based on the use of acidifying fertilizers, chemical forms offering good bioavailability, the fractionation of the intakes and the balance of the formulas, will make it possible to optimize the fertilization to achieve high yields [21].…”
Section: Introductionmentioning
confidence: 99%